Prevention of metallic corrosion by thiocarbohydrazides and their salts in vapor phase environment - Ansari F.A.; Quraishi M.A. (My University, 2025)
There are several ways to prevent atmospheric corrosion of metals and alloys. The use of vapor phase corrosion inhibitors (VCIs) has advantages over classical methods of corrosion prevention due to its low cost, practicability, accessibility, and reliability. Few vapor phase corrosion inhibitors have been synthesized by the reaction of thiocarbohydrazides and organic acids. The VCIs inhibiting action on mild steel was investigated by weight loss and potentiodynamic polarization methods. Sodium chloride inoculation and sulfur dioxide (SO2) were also carried out. The corrosion-inhibiting properties of these compounds have been found to depend on the nature of organic acids and thiocarbohydrazides. Thiocarbohydrazide cinnamate salt exhibited >90% inhibition efficiency even at a concentration of 250 ppm. All the compounds investigated brought down the corrosion current significantly and showed predominantly anodic behavior. © Taylor & Francis Group, LLC.